Green Bioconversion of Asbuton Bitumen into Hydrocarbon-Rich Oil by Trichoderma sp. Based on GC–MS Characterization - A. Johan; I. Sulistiyani; A. L. Giri Toba; A. H. Watoni; L. O. A. Nur Ramadhan; C. Baskar; L. O. Ahmad (International Journal of Acta Material, 2026)
This study presents a green bioconversion process for upgrading Buton natural bitumen (Asbuton) into hydrocarbon-rich bio-oil using Trichoderma sp. as a biological catalyst under mild conditions. The effects of composition ratio and incubation time on oil yield and physicochemical properties were investigated. The optimum condition was achieved at a 2:5 bitumen-to-fungus ratio after 25 days of incubation, producing a 4.74% yield with a density of 0.949 g cm⁻³, a viscosity of 3.83 Pa·s, a flash point of 69.6 °C, and a calorific value of 5412 Cal.g⁻¹. GC–MS analysis revealed forty peaks dominated by C16–C18 fatty acids, confirming the partial oxidative–hydrolytic depolymerization of asphaltic hydrocarbons into oxygenated aliphatic molecules. The decrease in viscosity and the appearance of long-chain fatty acids indicated efficient enzymatic degradation of heavy asphaltenes. These findings demonstrate that Trichoderma sp. effectively converts solid Buton bitumen into bio-oil under ambient conditions, highlighting its potential as a green, low-energy alternative for sustainable biofuel production.